CÓMO SALVAR EL MUNDO INTENTANDO NO LLEGAR TARDE A CLASE: EL VIAJE DEL HÉROE ADOLESCENTE EN LAS SERIES RUNAWAYS Y CAPA Y PUÑAL - Dr. Pablo SÁNCHEZ LÓPEZ, (Fonseca, Journal of Communication, 2023)
The 21st century has witnessed the rebirth or rediscovery of the classical superhero stories, thanks to the success of the Marvel Cinematic Universe. However, this success has been replicated, so far, into other screens such us TV. Moreover, the serialized television format has allowed Marvel to show other kind of tales not so suitable for the big screen.We are talking about narratives of teen superheroes, inspired by the comic-book sidekick tradition